The The First Occurrence of Mafic Alkaline Rock (Lamproite) in The Mamuju District, West Sulawesi, Indonesia: Implications for The REE and Critical Elements Enrichment - Fadlin Fadlin; Shaban Godang; Arifudin Idrus; Hill Gendoet Hartono; Januar Aziz Zaenurrohman; Raden Muhammad Asfaro; Wildan Nur Hamzah; Hernani Vitorino Nhatinombe (Indonesian Journal on Geoscience, 2026)
Mafic alkaline igneous rocks, along with their weathering products, are a significant source of Rare Earth Elements (REEs) and critical elements. One of the mafic alkaline rock-related REE and critical element sources is lamproite. Various methods were utilized in this study, including optical microscopy, X-ray diffraction (XRD), and scanning electron microscopy with Energy Dispersive Spectroscopy (SEM-EDS), as well as whole-rock geochemical analyses using X-ray fluorescence (XRF) and Inductively Coupled Plasma Mass Spectrometry/Optical Emission Spectroscopy (ICP-MS/OES). Based on mineralogical observations, it has been confirmed that the dykes from West Sulawesi are orendite-type lamproite rocks. Sanidine, phlogopite, diopside, and aegirine are the main minerals found in these rocks, including apatite and oxide minerals as accessory minerals. The dykes' whole-rock geochemistry indicates an ultrapotassic nature with a K₂O/Na₂O ratio > 3. Lamproite dykes display an increase in the large ion lithophile elements (LILEs) and a decrease in Ti, Sr, and P, with minimal Eu anomalies. They also show an increase in the light rare earth elements (LREEs), ranging from 901 to 1558 ppm, and a significantly higher content of Zr (968-3083 ppm), Th (152-408 ppm), and U (30-37 ppm). The dykes are related to an orogenic lamproite that formed during post-collisional tectonic continental extension. It contained a significant amount of REE-Zr-Th-bearing minerals, such as apatite (La-Ce-Nd), zirconosilicate (Zr-Ce), and Ba-perovskite (Zr-Th-Ce-Tb). The enrichment of light rare earth elements (LREEs), thorium (Th), and zirconium (Zr) in these dykes can be attributed to both primary and secondary enrichment processes, such as metasomatism and hydrothermal alteration. This phenomenon is evidenced by mineral replacement textures or pseudomorphs, as well as a skeletal texture resulting from rapid cooling in a hydrothermal fluid environment. Therefore, understanding the formation of mafic alkaline rocks, especially lamproite, and their role in enriching REEs and critical elements is a crucial future scientific goal.